The largely unnoticed spread of Clostridioides difficile PCR ribotype 027 in Germany after 2010 - Vanda Marujo; Mardjan Arvand (Elsevier, 2020)
Summary: In recent decades, incidence and severity of Clostridioides difficile infection (CDI) has increased dramatically, coinciding with the emergence of hypervirulent strains such as PCR ribotype 027 (RT027). Data on prevalence of distinct C. difficile strains in random CDI cases in Germany are scarce. The aim of this review was to obtain an overview of prevalence and geographical distribution of RT027 among clinical C. difficile isolates from random cases in non-outbreak settings in hospitals in Germany. For this purpose, we performed a literature review on reported cases of C. difficile RT027 in Germany between 2007 and 2019 in three databases (PubMed, Embase and LIVIVO) and conference proceedings. Studies with selection bias for RT027 (e.g. clinical severity, outbreak reports) were excluded. A total of 304 records were screened, from which 21 were included in this analysis. The nationwide prevalence of RT027 in Germany was <1% prior to 2010 but increased continuously thereafter, reaching 21.7% in 2013. The regional prevalence varied markedly between federal states, higher prevalence was reported from North Rhine-Westphalia (37.4%) and Saxony (31.8%) in 2013-2015. However, data on C. difficile RT027 were not available from almost half of the federal states and were scarce at the national level. Our data suggest a remarkable spread of RT027 in Germany during the past decade, which has remained rather unnoticed so far. A national program for molecular surveillance of C. difficile is required to monitor the changing epidemiology of CDI and to adjust the prevention and control measures.